Correct Positioning of Percutaneous Iliosacral Screws With Computer-Navigated Versus Fluoroscopically Guided Surgery in Traumatic Pelvic Ring Fractures. Issue 6 (June 2016) - Verbeek, Jan; Hermans, Erik; van Vugt, Arie; Frölke, Jan Paul
Abstract : Objectives: To assess the correct positioning of iliosacral screw in patients with unstable traumatic pelvic ring injury by comparing fluoroscopically guided computer-navigated surgery (CNS) with conventional fluoroscopy (CF) through reviewing postoperative computed tomography (CT) and clinical indicators. Design: A comparative multicenter cohort study. Setting: Two level I Trauma Centers in the Netherlands. Patients: The computer-navigated group (n = 56) and the CF group (n = 24) were comparable regarding age (mean, 43 years), sex (58%, male), body mass index (25 kg/m 2 ), injury severity score (27), injury-to-surgery interval (7 days), and Orthopaedic Trauma Association classification (40% 61-B, 60% 61-C). Main Outcome Measurements: The position of the iliosacral screws was evaluated on postoperative CT. In addition, clinical morbidity and reoperation were assessed. Results: In the CNS group, a total of 111 screws were placed (2.0 per patient), of which 83% were placed correctly. In the CF group, 39 screws (1.6 per patient) were placed, 82% of them correctly. Inadequate fixation included neural foramina hit [12 screws (11%) in the CNS group versus 3 screws (8%) in the CF group, P = 0.76] and extraosseous dislocation [7 screws (6%) vs. 4 screws (10%), respectively, P = 0.47]. Five patients required reoperation, all in the CNS group, P = 0.32. We observed more adequate positioning with increased surgical experience, P = 0.12. Conclusions: In contrast to what has been suggested by previous studies, we found no benefit from computer-navigated iliosacral screw fixation compared with fluoroscopically guided surgery regarding the correct positioning of iliosacral screw on postoperative CT and related morbidity. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.